Surface modification of activated carbon for enhancement of heavy metals adsorption. - Onundi, Yusuf Bamidele; Al-Mamun, Abdullah; Al-Khatib, Ma'an Fahmi Rashid; Ahmed, Yehya M.; Al-Saadi, Mohammed A. (2010)
Carbon nanotubes were synthesized on granular activated carbon (CNT-GAC) to enhance its adsorption capacity was used as adsorbent. This work involved the characterization of the new material using FESEM, TEM and FTIR. Characterization revealed the morphology of CNT on GAC as multiwalled CNT with average outer diameter of 50 nm. Laboratory experimental investigation on the effect of pH, contact time on lead, copper and nickel adsorption from a mixed metals solution was carried out. Adsorption experiments at constant room temperature were carried out using CNT-GAC as adsorbent and fitted to Langmuir and Freundlich models. Results showed that pH 5 was the most suitable and equilibrium metal concentration was observed at 60 minutes contact time. It was noted that the sorption capacities corresponding to equilibrium varied for each metal, with lead recording 99%, copper 61% and nickel 20%, giving metal affinity trend of Pb> Cu>Ni on the CNT-GAC. Langmuir model having higher R2 value of 0.926, 0.889 and 0.986 for copper, nickel and lead adsorption was better than Freundlich in predicting the adsorption process of the three metals from the mixed metals solution